Development of chitosan/bentonite hybrid composite to remove hazardous anionic and cationic dyes from colored effluents. Issue 3 (September 2016) - Dotto, G.L.; Rodrigues, F.K.; Tanabe, E.H.; Fröhlich, R.; Bertuol, D.A.; Martins, T.R.; Foletto, E.L.
Graphical abstract: Highlights: A hybrid composite chitosan/bentonite (CBC) was developed to adsorb dyes. CBC presented adequate mechanical, textural and physicochemical characteristics. The adsorption capacities were of 362.1 mg g −1 for AR and 496.5 mg g −1 for MB. CBC can be reused three times for AR and two times for MB. CBC presented high adsorption capacities for anionic and cationic dyes. Abstract: Chitosan/bentonite hybrid composite (CBC) was developed and successfully applied to remove anionic (Amaranth Red (AR)) and cationic (Methylene Blue (MB)) dyes from colored effluents. The influence of several factors on the dyes adsorption capacity was investigated. Kinetic, equilibrium and thermodynamic viewpoints were elucidated. Desorption and reuse studies were performed. It was found that CBC presented a heterogeneous structure with good mechanical and swelling properties, which facilitates the phase separation after adsorption. The adsorption was favored at pH 2 for AR and 10 for MB. Elovich model was the more adequate to represent the kinetic data. The equilibrium data followed the Langmuir model, being the maximum adsorption capacities of 362.1 mg g −1 for AR and 496.5 mg g −1 for MB. The adsorption process was spontaneous, favorable and exothermic. Desorption and reuse was possible three times for AR and two times for MB, maintaining the same adsorption capacity. These results demonstrated that chitosan/bentonite hybrid composite is an advanced adsorbent with advantages, such as, easy phase separation, capability to remove anionic and cationic dyes and potential for reuse.